Genome Sequence of Bacillus anthracis Strain Tangail-1 from Bangladesh - Rume, Farzana Islam (Genome Announc, 2016)
Soil was collected in July 2013 at a site where a cow infected with anthrax had been the month before. Selective culturing yielded Bacillus anthracis strain Tangail-1. Here, we report the draft genome sequence of this Bacillus anthracis isolate that belongs to the canonical A.Br.001/002 clade.